Peran Self-efficacy Terhadap Prokrastinasi Mahasiswa pada Pembelajaran Online di Kota Bukittinggi - Nofriadi Syahnur (Universitas Negeri Padang, 2022)
Procrastination can be described as an activity to procrastinate work. Self-efficacy can be a component to consider procrastination behavior. Self-efficacy also plays an important role in determining whether an individual is capable of completing tasks that have an influence on the goals to be achieved. This study aims to determine the role of self-efficacy on student procrastination in online learning in the city of Bukittinggi. The research method used is quantitative research using a descriptive correlational approach. Respondents of this study were 66 students in the City of Bukittinggi. To obtain data, researchers used a Likert scale in the form of a self-efficacy measurement tool and a procrastination measuring tool. The data analysis technique uses multiple regression analysis techniques with SPSS 16.0 for windows applications. The results of the research data analysis obtained r = - 0.364 with a level of p = 0.003 (p <0.05). The significant effect of self-efficacy on procrastination is r2 = 13.0%. This study proves that there is a positive relationship between self-efficacy and student procrastination in online learning in the City of Bukittinggi.